2008
DOI: 10.1002/hbm.20437
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy: Differential pattern of damage in temporopolar cortex and white matter

Abstract: Our purpose was to quantify structural changes of the temporopolar cortex (TPC) and its white matter (TPWM) in temporal lobe epilepsy (TLE) using MRI volumetry and texture analysis. We studied 23 patients with hippocampal atrophy, and 20 healthy controls. Gradient magnitude and entropy were calculated to model signal intensity blurring on T1-MRI. Two observers assessed signal changes and atrophy visually. Compared to controls, TLE patients had a decrease in TPC and TPWM volume ipsilateral to the seizure focus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 78 publications
1
14
0
4
Order By: Relevance
“…The correct identification of hippocampal sclerosis with proton-attenuation MR images was achieved by using f 9 and f 3 , whereas a total of 9 T2-weighted MR image features were able to correctly classify the hippocampi. In a subsequent study, Sankar et al 46 discovered decreased gradient and f 9 features in patients with epilepsy, connoting a blurring of the temporopolar WM (65% sensitivity and 100% specificity for hippocampal atrophy versus 17% and 69% with visual assessment).…”
Section: Epilepsymentioning
confidence: 98%
“…The correct identification of hippocampal sclerosis with proton-attenuation MR images was achieved by using f 9 and f 3 , whereas a total of 9 T2-weighted MR image features were able to correctly classify the hippocampi. In a subsequent study, Sankar et al 46 discovered decreased gradient and f 9 features in patients with epilepsy, connoting a blurring of the temporopolar WM (65% sensitivity and 100% specificity for hippocampal atrophy versus 17% and 69% with visual assessment).…”
Section: Epilepsymentioning
confidence: 98%
“…Studies based on manual volumetric MRI analysis largely confirmed previous histological assessments, and provided a more comprehensive picture of the regional extent of structural abnormalities in TLE. Volumetric analysis demonstrated atrophy in multiple limbic structures, including the hippocampus, entorhinal cortex, amygdala (Cendes et al, 1993a,b; Bernasconi et al, 2001, 2003a,b), temporopolar, perirhinal, lateral temporal neocortices (Jutila et al, 2001; Moran et al, 2001; Sankar et al, 2008), and the thalamus (Dreifuss et al, 2001; Natsume et al, 2003; Bernhardt et al, 2012). In the hippocampus and thalamus, surface shape mapping has furthermore allowed localizing structural anomalies at a subregional level (Hogan et al, 2004; Kim et al, 2008; Bernhardt et al, 2012, in press).…”
Section: Regional Patterns Of Structural Pathologymentioning
confidence: 99%
“…TA has potential for clinical use, providing information on many neurological disorders. Indeed, it has been used to study intracranial brain tumors, epilepsy, multiple sclerosis, Alzheimer's disease, and amyotrophic lateral sclerosis (ALS) …”
mentioning
confidence: 99%